Status of Foreign Aid to Nepal’s Earthquake-2015 - K. Shakya (Lowland Technology International, 2020)
Nepal is victimized by different types of natural disasters, likeearthquakes landslides, floods and others. On 25th April and May12th, 2015, Nepal had 7.8 and 7.3 magnitude respectivelyearthquakes that struck central of Nepal. The objective of thepaper focuses on status of foreign aid to Nepal’s earthquake-2015. The paper presents the donor’s commitment anddisbursement during the earthquake -2015 in Nepal. Therefore,the study is descriptive, analytical and exploratory. The study isbased on secondary data information from different sources.The powerful tremor and aftershocks led to the loss of close to9,000 lives, injured over 23,000 people, fully destroyed over half amillion homes, displaced over 60,000 people. It resulted in totaleconomic losses of approximately US$ 9 billion. It has been foundthat altogether 34 countries physically responded to the disaster,17 of which sent their respective military teams to assist in theimmediate search and rescue phase. Bilateral aid in terms ofrelief items as well as financial aid was received fromapproximately 70 countries worldwide. There is a hugecommitment and disbursement of foreign aid to earthquake’sNepal-2015. However, it has been found that the commitmentsare much higher than disbursement in earthquake- 2015 inNepal. Although, after two years of the earthquakes, only abouthalf the money pledged to Nepal by donors